Digital Art History: The Questions that Need to Be Asked. (3rd April 2019) - Rodríguez-Ortega, Nuria
Abstract : This paper provides a critical overview of the evolution of the field of digital art history since the 2013 special issue of Visual Resources dedicated to digital art history. I particularly review the narratives and results that have been generated during the development of this specific field of research, examining to what degree these can or should be re-evaluated in light of the post-digital society in which we find ourselves, and as part of post-humanistic thinking. Thus I combine a historical overview with a prospective focus on digital art history in the years to come.